IMPLEMENTATION OF VALUE STREAM MAPPING (VSM) TO INCREASE PRODUCTIVITY OF ASSEMBLY PRODUCTION LINE - Ferdian, Rendiyatna; Anwar, Asep (CENTRAL ASIA AND THE CAUCASUS, 2022)
As a manufacturing company, PT. ABC has plans to create a new lean production line of product X. They did it to fulfill customer demand and be able to compete with other manufacturing company. Current performance shows that there is an average of 2% products that through a rework process, in which 95% of it can still be reused. In this research, we try to proposed a design of production line by applying Value Stream Mapping (VSM) in the process. Based on the results of data processing that has been carried out, it can be seen that the application of VSM in the production process can identify the process of waste that occurs easily. With its application can provide an average increase in productivity for the assembly line by 92.5% and an increase in productivity about 167% compared to the previous layout.